Again!!. No. 5 - Kubo, Mitsurou, 1975- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
"Having seen Usami's lonely fate after the collapse of the ouendan, Kinichiro returns to the past again, more determined than ever. He flat-out tells Usami about his time traveling, and the two hatch their plan to change destiny. But when their newfound closeness is misunderstood, it sets off a gossip bomb that threatens to destroy everything. Has all of Kinichiro's time traveling been for naught?"--